(untitled) (CIPEEX, 2025)
Socio-emotional education has gained increasing recognition as a fundamental pillar in the holistic development of children and adolescents. In a world that is ever more complex and interconnected, the ability to identify, understand, and manage one’s own emotions, as well as to develop empathy and social skills, becomes crucial for both individual and collective well-being (Colagrossi & Vassimon, 2017). This study analyzes the importance of including an emotions scavenger hunt in the school environment, aiming to promote children’s socio-emotional development. It is an integrative literature review, conducted through studies and analyses of scientific articles, prioritizing works that emphasize playfulness and socio-emotional skills. The review found that introducing the emotions scavenger hunt in schools aims not only at teaching emotions such as joy, sadness, anger, fear, surprise, and love, but also at fostering empathy, self-awareness, respect for differences, and healthy relationships among children. The use of such playful activities in the school context contributes to shaping more balanced, aware individuals who are better prepared for the challenges of life in society